A continental approach to estimate the area required for proposed wind-power parks and their overlap with protected areas in Africa - Jana Mayer; Rebecca Peters; Jens Bange; Moritz Mauz; Andreas Platis; Christiane Zarfl (Environmental Research Letters, 2025)
Wind energy (WE) is one of the key renewable energy technologies required to transform the energy sector to reduce climate change. In the global expansion of WE, one main concern is that wind-power parks (WPPs) take up large areas of land, causing conflicts with other uses such as nature conservation. Existing impact analyses for WPPs are mostly restricted to case studies, and it lacks studies that investigate potential impacts at a larger scale because no scientific consensus on the area associated to a WPP exists. This study proposes a continental, GIS-based approach to estimate the area required for proposed onshore WPPs and to estimate their potential overlap with protected areas (PAs) on the African continent. The results of the spatial analysis show that, in total, the currently proposed 149 WPPs would require 852 km ^2 of land on the African continent, thereof 11 would overlap with PAs. The overlaps sum up to an area of 42 km ^2 , which corresponds to an affected nominal power of 834 MW (5% of the total projected wind power capacity). These findings reveal the need for further purposefully local in-depth analyses to investigate if the WPP can be operated in accordance with the conservation of the PA. This work provides new data and a transferable methodological approach on the expansion of WE and its potential space requirement and contributes to the investigation of potential land-use conflicts of proposed onshore WPPs on a broader scale.